Inhibition of Pseudomonas aeruginosa biofilm formation and expression of virulence genes by selective epimerization in the peptide Esculentin‐1a(1‐21)NH2. (13th June 2019) - Casciaro, Bruno; Lin, Qiao; Afonin, Sergii; Loffredo, Maria Rosa; de Turris, Valeria; Middel, Volker; Ulrich, Anne S.; Di, YuanPu Peter; Mangoni, Maria Luisa
Abstract : Pseudomonas aeruginosa is a pathogenic bacterium known to cause serious human infections, especially in immune‐compromised patients. This is due to its unique ability to transform from a drug‐tolerant planktonic to a more dangerous and treatment‐resistant sessile life form, called biofilm. Recently, two derivatives of the frog skin antimicrobial peptide esculentin‐1a, i.e. Esc(1‐21) and its D‐amino acids containing diastereomer Esc(1‐21)‐1c, were characterized for their powerful anti‐ Pseudomonal activity against both forms. Prevention of biofilm formation already in its early stages could be even more advantageous for counteracting infections induced by this bacterium. In this work, we studied how the diastereomer Esc(1‐21)‐1c can inhibit Pseudomonas biofilm formation in comparison to the parent peptide and two clinically‐used conventional antibiotics, i.e. colistin and aztreonam, when applied at dosages below the minimal growth inhibitory concentration. Biofilm prevention was correlated to the peptides' ability to inhibit Pseudomonas motility and to reduce the production of virulent metabolites, for example, pyoverdine and rhamnolipids. Furthermore, the molecular mechanism underlying these activities was evaluated by studying the peptides' effect on the expression of key genes involved in the virulence and motility of bacteria, as well as by monitoring the peptides' binding to the bacterial signaling nucleotide ppGpp. Our results demonstrate that the presence of only two D‐amino acids in Esc(1‐21)‐1c is sufficient to downregulate ppGpp‐mediated expression of biofilm‐associated genes, presumably as a result of higher peptide stability and therefore prolonged interaction with the nucleotide. Overall, these studies should assist efficient design and optimization of new anti‐infective agents with multiple pharmacologically beneficial properties. Abstract : In aqueous environment, the AMP Esc(1‐21)‐1c prevents bacterial biofilm formation, by reducing the availability of the free nucleotide ppGpp. This leads to downregulation of the expression of virulence genes, thus hindering bacterial motility.